Period change investigation of the low mass ratio contact binary BO Ari - W. Kriwattanawong (2018)
© 201 5Elsevier B.V. All rights reserved. A photometric study and period change analysis for the A-type low mass ratio contact binary BO Ari is presented. The BVR light curves were fitted by using the Wilson-Devinney method. The photometric solution yields a low mass ratio of q = 0.1754(±0.0016) with a contact degree of f = 27.72%(±2.37%). We found a long-term orbital period decrease at a rate of dPdt=-3.49×10-7d yr-1. This result indicates that the system is undergoing mass transfer from the primary component to the secondary with a mass transfer rate of m1m1= -7.77×10-8yr-1. With the period decrease, the inner and outer critical Roche surfaces will tighten and cause the degree of contact to increase. Therefore, BO Ari may evolve into a deeper contact system.